Calculation of the Mathematical Model of the Linear Motor - Molis, M.; Matkevičius, E.; Radzevičius, L. (Elektronika ir Elektrotechnika, 2009)
Development of the mathematical model of the linear electromagnetic motor and the dependencies of the inductance and traction force on the secondary element position expressed by mathematical equations, are presented. The dependency of the inductance on the secondary element position was obtained, approximating the inductance change diagram obtained experimentally. Also, using the theory of electromechanical energy transformation, mathematical expressions of the dependency of the traction force on the secondary element position were obtained. Mathematical model of the linear electromagnetic motor is composed of the system of differential equations. The Runge-Kutta calculation method was used to solve these equations. The transitional processes of the current, speed, secondary element position, and dynamic traction force components were obtained with the solution of the system of differential equations. All obtained results of the dependencies and transitional processes of the mathematical model are presented in the graphic form. In accordance with the obtained results of the mathematical model the conclusions were formulated, specifying electromagnetic properties of the linear electromagnetic motor. Ill. 6, bibl. 7 (in English; the summaries in English, Russian and Lithuanian).